Características antropométricas e de aptidao física de meninos atletas de futebol - da Luz Canhadas, I.; Pignataro Silva, R.; Rodrigues Chaves, C.; Andrews Portes, L. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2010)
The objective of this study was to determine anthropometric and physical fitness characteristics of Brazilian male children and adolescents at the beginning of soccer training. In this study, 282 male soccer players ranging in age from 10 to 13 years were evaluated. The athletes participated in a formal soccer training program 3 times per week, with each training lasting 3 hours. Anthropometric and physical fitness parameters were obtained. The boys were divided into age classes and prevalence data were analyzed using Pearson`s chi-square test. Parametric data were compared by one-way ANOVA or the Kruskal-Wallis test, when necessary. The results are expressed as the mean ± standard deviation and a p value <0.05 was considered to be significant. Growth, development, body adiposity and physical fitness characteristics were adequate and proportional to age among the boys studied (p<0.05). It was concluded that anthropometric and physical fitness characteristics of young male elite soccer players improve with and are proportional to age. Children and adolescents greatly benefit from regular physical activity. The present results show that young male soccer players present adequate anthropometric conditions and physical fitness prior to the initiation of formal training at soccer clubs.